Use of cardiac troponin I (cTnI) levels to diagnose severe hypoxia and myocardial injury induced by perinatal asphyxia in neonatal dogs - Nobre Pacífico Pereira, Keylla Helena [UNESP]; Hibaru, Viviane Yukari [UNESP]; Fuchs, Kárita da Mata [UNESP]; Cruz dos Santos Correia, Luiz Eduardo [UNESP]; Lopes, Maria Denise [UNESP]; Ferreira, João Carlos Pinheiro [UNESP]; Ferreira de Souza, Fabiana [UNESP]; Machado, Luiz Henrique de Araújo [UNESP]; Chiacchio, Simone Biagio [UNESP]; Gomes Lourenço, Maria Lucia [UNESP] (Elsevier, 2022)
Prolonged perinatal asphyxia and subsequent severe hypoxia are the main causes of mortality in neonatal dogs in the first days of life. In medicine, specific cardiac biochemical markers, such as troponin I, are used to diagnose ischemic and nonischemic myocardial injury in asphyxiated newborns after birth. Thus, the objectives of this study were to compare the levels of cardiac troponin I (cTnI) between asphyxiated and nonasphyxiated newborn dogs and evaluate the correlations of cTnI levels with the modified Apgar score, the levels of oxygen saturation, blood glucose, and lactatemia, and blood gas parameters. This study aimed to determine the possible use of cTnI as a marker of severe hypoxia and myocardial ischemic injury in neonatal dogs. Fifteen animals in a eutocic vaginal delivery group (VG), 15 animals in a cesarean section group (CG), and 13 animals in a hypoxia (asphyxiated) group (HG) were evaluated. The animals in the asphyxiated group were from dystocic deliveries and born by vaginal delivery or cesarean section. All groups were evaluated at birth and after 60 min. The newborns in the VG and CG exhibited mixed acidosis (respiratory acidosis due to increased partial pressure of CO2 (pCO2) and metabolic acidosis due to reduced pH and bicarbonate (HCO3) levels, base excess/deficit in the extracellular fluid compartment (BEecf), and increased lactate levels) due to transient physiological hypoxemia at birth. The cTnI levels in the VG and CG were within the reference standards for healthy dogs. No correlations between cTnI level and the other parameters were observed in the VG and CG. Newborns in the HG exhibited prominent mixed acidosis (p < 0.05) due to severe hypoxemia. The Apgar score and blood gas parameters showed that these dogs were born asphyxiated, and they presented low vitality and the need for resuscitation maneuvers. The cTnI levels in the HG were significantly higher than those in the VG and CG (p < 0.05) and above the reference standards for healthy dogs, which indicated ischemic myocardial injury. The cTnI level was negatively correlated (p < 0.05) with the parameters Apgar score, heart rate, peripheral oxygen saturation (sO2) level, reflex score, and total carbon dioxide (TCO2) level and positively correlated (p < 0.01) with lactate level. This study showed that asphyxiated newborn dogs have higher serum cTnI levels than nonasphyxiated newborn dogs; thus, the cTnI can be used as a marker of severe hypoxia and ischemic myocardial damage in newborn dogs.
Keywords: Apgar score; Cesarean section; Hypoxemia; Myocardium; Puppies